Spotify Podcast Become a New Learning Mean for Youth - Muhammad Sulton Al Fatih; Muhammad Luthfie; Ali Alamsyah Kusumadinata (Universitas Djuanda, 2022)
The development of technology, especially in the field of communication, has experienced a significant change in the practice of consuming information or content, teenagers who are not included in the adult/older group or children, are vulnerable to being affected by the new media they consume, one form of digital technology that is developing are podcasts. Spotify podcast is a new medium in the consumption of information or content. The nature of podcasts that can be used freely by teenagers will affect them in social and even educational aspects. The widespread use of podcasts among teenagers makes it a new means of learning. The main problem in this research is how the Spotify podcast becomes a new learning tool for teenagers. The purpose of the study was to find out how Spotify's podcast became a new learning tool for teenagers. Using qualitative research methods, primary data in the form of questionnaires distributed via google form to the youth of Bogor City, and secondary data is the result of previous research. Using descriptive analysis, observations were made with direct observation of the results of the questionnaires that had been collected. The results obtained in this study show that Spotify podcasts are a new educational tool for teenagers that contain elements of education in it, formal or non-formal, packaged in a concise and entertaining way. This research can be a recommendation for lecturers, especially lecturers at the University of Djuanda, to apply the new Spotify podcast media in teaching and learning activities